Effects of 5-aminolevulinic acid photodynamic therapy for cervical low-grade squamous intraepithelial lesions with HR-HPV infections - Li, Yu; Chen, Jing; Hu, Yan; Xu, Qingyang; Jiang, Rongzhen; Teng, Yincheng; Xu, Yanli; Ma, Li (Frontiers in Medicine, 2024)
Objective To determine the effectiveness and safety of 5-aminolevulinic acid mediated photodynamic therapy (5-ALA PDT) in HR-HPV infected patients with cervical low-grade squamous intraepithelial lesions (LSIL) and to explore possible factors affecting treatment outcomes. Methods This retrospective study included 96 patients with histologically confirmed cervical LSIL and high-risk human papillomavirus (HR-HPV) infection. They received 5-ALA PDT treatment once a week for a total of 3 courses. All patients were evaluated by cytology tests, HPV DNA assay, colposcopy, and biopsy at 2 weeks, 3 months, and 6 months checkpoint. The chi-square test were used to evaluate the differences in various clinical data, and a p value <0.05 was considered statistically significant. Results At 2 weeks, 3 months, and 6 months checkpoint, colposcopies showed that the cervical iodine-unstained area under VILI (visual inspection with Lugol’s iodine) significantly reduced (p < 0.01) with no structure changes. At 3 months and 6 months checkpoint, the pathological regression rate reached 87.5% (84/96) and 94.79% (91/96), while the HR-HPV clearance rates reached 80.21% (77/96) and 93.75% (90/96) respectively. We also examined the efficacy in the HPV 16/18-related group and non-HPV 16/18-related group. The HR-HPV clearance rate in the HPV16/18 group [94.87% (37/39)] was significantly higher than that of the non-HPV 16/18 group [70.17% (40/57)]. However, at 6 months after treatment, the clearance rate of the HPV 16/18 group [94.87% (37/39)] showed no statistical difference from the non-HPV 16/18 group [92.30% (53/57)]. Conclusion Topical 5-ALA PDT can effectively eliminate HR-HPV infection and treat low-grade cervical squamous intraepithelial lesions, it offers an alternative treatment option for patients with LSIL, especially for those with fertility requirements and who wish to preserve cervical structure or function.